Analisis Strategi BSI Kcp Stabat Proklamasi dalam Meningkatkan Minat Nasabah Menggunakan Pembayaran Berbasis Qris - Amanda, Feby Aulia; Tambunan, Khairina (Medan Resource Center, 2022)
Bank Syariah Indonesia KCP Stabat Proclamation has various payment systems, one of which is the QRIS payment system. QRIS means the payment system uses the QR Code method belonging to Bank Syariah Indonesia whose payment uses a barcode scan owned by Bank Syariah Indonesia. After 2020, due to regulations from Bank Indonesia (BI) regarding Queck Response Code Indonesia (QRIS), which is the standardization of payments using the QR Code method, it becomes easier, faster and maintains security for banking or Islamic banking & E-Commerce in Indonesia. QRIS at Bank Syariah Indonesia, which is one of the features of the Mobile Banking service, applies a regulatory account using a wadiah & mudharabah contract. This study means identifying the BSI KCP Stabat Proclamation Strategy to Increase Client Interest in Using QRIS-Based Payments. This study is a field study using a descriptive qualitative study method. There is also the value of this study from the staff of Bank Syariah Indonesia KCP Stabat Proclamation. The procedure for collecting data is using questions and answers. The procedure for legalizing the data by using data & news according to various different roots.